2015
DOI: 10.1038/gim.2014.208
|View full text |Cite
|
Sign up to set email alerts
|

Training future physicians in the era of genomic medicine: trends in undergraduate medical genetics education

Abstract: PURPOSE: Advances in genomic technologies are transforming medical practice, necessitating the expertise of genomically-literate physicians. This study examined 2013-2014 trends in genetics curricula in US and Canadian medical schools to ascertain whether and how curricula are keeping pace with this rapid evolution. METHODS: Medical genetics course directors received a 60-item electronic questionnaire covering curriculum design, assessment, remediation of failing grades, and inclusion of specific topics. RESUL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 34 publications
6
81
0
1
Order By: Relevance
“…Furthermore, the current medical practice is outpaced by the rapid advancement of health science and technology. A recent survey on genetic curricula in USA and Canadian medical schools found that only 26 % responders reported formal genetic teaching during third and fourth year of school, and most responders felt the amount of time spent on genetics was insufficient for future clinical practice in this era of genomic medicine [3]. Not only medical educators felt the current medical education lags, students at Harvard Medical School expressed similar sentiment [4].…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, the current medical practice is outpaced by the rapid advancement of health science and technology. A recent survey on genetic curricula in USA and Canadian medical schools found that only 26 % responders reported formal genetic teaching during third and fourth year of school, and most responders felt the amount of time spent on genetics was insufficient for future clinical practice in this era of genomic medicine [3]. Not only medical educators felt the current medical education lags, students at Harvard Medical School expressed similar sentiment [4].…”
Section: Introductionmentioning
confidence: 97%
“…Most medical schools in Canada and the United States were shown to devote an average of 36 hours (with a range of 18-102 hours) of teaching to medical genetics with the most commonly taught topics being cancer genetics, Mendelian disorders, cancer genetics, multi factorial inheritance, clinical cytogenetic, and patterns of inheritance [10]. These lectures are usually delivered in the first year or two of preclinical medical training and this curriculum has not changed much in the last decade.…”
Section: Current State Of Genetics Education For Physiciansmentioning
confidence: 99%
“…Since the completion of the Human Genome Project, there is a growing recognition worldwide of the importance of genetics education for physicians [6][7][8] As a result, there have been studies on how and when genetics is taught in the medical curriculum [9,10]. Most medical schools in Canada and the United States were shown to devote an average of 36 hours (with a range of 18-102 hours) of teaching to medical genetics with the most commonly taught topics being cancer genetics, Mendelian disorders, cancer genetics, multi factorial inheritance, clinical cytogenetic, and patterns of inheritance [10].…”
Section: Current State Of Genetics Education For Physiciansmentioning
confidence: 99%
“…, NP Ambulos Jr 2,5 , AR Shuldiner 2,6 and MG Blitzer 2,7 Genetic and genomic discovery is revolutionizing medicine at an extraordinary pace, leading to a better understanding of disease and improved treatments for patients. This advanced pace of discovery presents an urgency to expand medical school curricula to include genetic and genomic testing (including pharmacogenomics), and integration of genomic medicine into clinical practice.…”
mentioning
confidence: 99%